Specifics of postinfarction interventricular septum rupture - Ursulenko, V. I.; Rudenko, M. L.; Zakharova, V. P.; Gordienko, M. M. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Objective. To develop the tactics and strategy of surgical treatment of PI IVSR in order to improve results, make algorithms depending on the severity, presence of heart failure and the time after the occurrence IVSR, examine the performance of intracardiac hemodynamics and state the optimum term intervention regarding the pathologies. Materials and Methods. We analyzed 65 cases of PI IVSR which were observed in the institute. Conclusions. PI IVSR usually occur during the first week following the myocardial infarction. Microscopic examination of the affected myocardial zone rupture of the IVS (revealed coagulation necrosis of cardiomyocytes with primary manifestation process organization. The formation of young connective tissue starting from the second week after the onset of PI IVSR. By the end of the third week, there are broad layers of connective tissue, which by the end of the first month form around gap scars that contain single lymphocyte infiltrates. There have morphological changes of the heart, including: a) different types of IVS rupture, b) myocardial injury of the IVS; c) coronary atherosclerosis varying severity; d) changing the geometry of the cavities of the heart. Surgical treatment should be applied on the basis of morphological changes of the heart. The method of surgical treatment is effective only if implementation of the correction of pathological changes in the heart, resulting PI IVSR.